Liposomes as a Novel Drug Delivery System: Fundamental and Pharmaceutical Application - Salimi, Anayatollah (Asian Journal of Pharmaceutics (AJP), 2018)
Liposomes are spherical vesicles consisting of one or more phospholipid bilayers, which are under extensive investigation as drug carriers for improving the delivery of bioactive agents and many different compounds in biological, pharmaceutical, and medical and nutritional research. The majority of those clinically approved have diameters of 50–300 nm. Among several talented new drug delivery systems, liposomes characterize an advanced technology to deliver active molecules to the site of action and reduce undesirable side effects improving its in vitro and in vivo activity, as well as reducing the toxicity of the drug and enhancing the efficacy of the encapsulated drug. The present review will briefly explain the characteristics, advantages, scalable techniques based on the type of produced liposomes and potential applications of liposomes in food, cosmetics, gen genetic engineering, immunology, cancer therapy, infection, and also the diagnosis.